Recent developments on triazole nucleus in anticonvulsant compounds: a review - Ming-Xia Song; Xian-Qing Deng (Taylor & Francis Group, 2018)
Epilepsy is one of the common diseases seriously threatening life and health of human. More than 50 million people are suffering from this condition and anticonvulsant agents are the main treatment. However, side effects and intolerance, and a lack of efficacy limit the application of the current anticonvulsant agents. The search for new anticonvulsant agents with higher efficacy and lower toxicity continues to be the focus and task in medicinal chemistry. Numbers of triazole derivatives as clinical drugs or candidates have been frequently employed for the treatment of various types of diseases, which have proved the importance of this heterocyclic nucleus in drug design and discovery. Recently many endeavours were made to involve the triazole into the anticonvulsants design, which have brought lots of active compounds. This work is an attempt to systematically review the research of triazole derivatives in the design and development of anticonvulsant agents during the past two decades.